Characterising U-232 and Tl-208 Buildup and Decay on Thorium-fuelled RGTT200K - R. Andika Putra Dwijayanto (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2021)
Thallium-208 (Tl-208), a decay daughter of uranium-232 (U-232), is a strong 2.6 MeV gamma emitter present in significant amount in thorium fuel cycle. Its existence enhances the anti-proliferation characteristics of thorium fuel cycle, but at the same time complicates the fuel handling system. In order to ensure that radiation hazard is properly contained, the buildup and decay characteristics of both U-232 and Tl-208 need to be understood. This paper aimed to provide a characterisation on U-232 and Tl-208 buildup in the thorium-fuelled RGTT200K, a 200 MWt very high temperature reactor (VHTR) developed by BATAN, using ORIGEN2.1 depletion code. Pure and impure U-233 were used as the fissile nuclide for comparison. The result showed that U-232 buildup rate is faster in pure U-233, but its Tl-208 buildup is slower. Nonetheless, pure U-233 always has its U-232 and Tl-208 activity lower than impure U-233. Accordingly, both U-232 and Tl-208 radioactivity post-discharge in pure U-233 are lower than impure U-233, although the difference become somewhat negligible after 300 years of decay. Tl-208 activity peaked after 10 years of decay, necessitating different approach in managing post-discharge fuel management.